Defining the Epithelial-to-Mesenchymal Transition and Regulation of Stemness in the Ovarian Surface Epithelium - Carter, Lauren (Université d'Ottawa / University of Ottawa, 2018)
The ovarian surface epithelium (OSE) is a monolayer of cells surrounding the ovary that is ruptured during ovulation. After ovulation the wound is repaired, however this process, and the mechanisms to maintain OSE homeostasis after the wound is repaired are poorly understood. We have shown the mouse OSE (mOSE) contains a stem cell population that is expanded by Transforming Growth Factor Beta 1 (TGFB1), a factor present in follicular fluid. These data suggest that components in the follicular fluid such as TGFB1 may promote wound repair and OSE homeostasis through maintenance of the OSE stem cell population. Additionally, TGFB1 may promote wound repair through induction of an epithelial-to-mesenchymal transition (EMT) and activation of pro-survival pathways, as seen in other tissues. To elucidate the mechanism for TGFB1-mediated ovulatory wound repair, mOSE cells were treated with TGFB1, which induced an EMT seen with increased Snai1 expression and cell migration. Snai1 overexpression also increased cell migration and sphere formation (a stem cell characteristic). RNA sequencing results suggest this is at least in part through elevated collagen deposition in SNAI1 overexpressing cells. A TGFB signalling targets array identified Cox2 induction following TGFB1 treatment. Constitutive Cox2 expression did not promote an EMT, but enhanced sphere formation and cell survival. Finally, TGFB1 treatment decreased Brca1 expression, which when deleted from mOSE cells also increased sphere formation. RNA sequencing results suggest that Brca1 deletion promotes stemness through activation of the stem cell genes Ly6a and Lgr5. RNA sequencing was also used to compare mOSE cells cultured as monolayers and as spheroids, with and without TGFB1. These results validate our findings that TGFB1 promotes an EMT partially through Snail induction and the upregulation of Cox2. mOSE cells cultured as spheroids acquire a mesenchymal transcriptional profile that is further enhanced with TGFB1 treatment. These data suggest that TGFB1 may promote ovulatory wound repair and maintain OSE homeostasis through the induction of an EMT, maintenance of the stem cell population and activation of a pro-survival pathway. Interestingly, mOSE spheroids also decrease Brca1 expression and upregulate cancer associated genes such as Pax8 and Greb1. The induction of survival pathways, while simultaneously increasing stemness and repressing Brca1 could render cells more susceptible to transformation. This work provides novel insights as to why ovulation is the primary non-hereditary risk factor for ovarian cancer.
Keywords: ovarian surface epithelium; ovulation; stemness; epithelial-to-mesenchymal transition; wound repair; Cox2; Brca1; Snai1